Secundum Atrial Septal Defect Closure via the Transhepatic Approach in a Patient With Situs Ambiguus and a Left-Sided Inferior Vena Cava. (September 2021) - Olagunju, Abdulbaril; Mihyawi, Nawfal; Moazez, Carmel; Roy, Ranjini Raina; Mehdizadeh, Azar; Saririan, Mehrdad
Secundum atrial septal defect (ASD) is the most common type of ASD. Symptoms including dyspnea on exertion usually manifest in the third and fourth decade of life. The transcatheter closure is the treatment of choice for secundum ASD. The transfemoral venous approach has been the mainstay. However, this approach can be challenging or impossible in patients with congenital absence or interruption of the inferior vena cava (IVC). The latter has been reported in patients with situs ambiguus and inversus. In this patient population, other forms of venous access such as the transjugular or transhepatic approach are used. We present a unique case of symptomatic secundum ASD in a patient who was incidentally found to have situs ambiguus with a left-sided intact IVC. An initial attempt at the ASD closure via the transfemoral approach was unsuccessful due to acute angulation. A repeat attempt was successful via the transhepatic approach with the guidance of real-time ultrasound, transesophageal echocardiogram, and the involvement of an interventional radiologist. The procedure was well tolerated without any complications. Repeat transthoracic echocardiogram with agitated saline the day after the procedure was negative for interatrial shunting.